2006
DOI: 10.1111/j.1469-0691.2006.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antimicrobial susceptibility patterns of Nocardia spp. from clinical specimens by Etest

Abstract: Susceptibilities to 11 antimicrobial agents were determined by Etest for 93 Nocardia isolates from clinical specimens and 15 type strains belonging to different Nocardia spp. All isolates were susceptible to trimethoprim-sulphamethoxazole, amikacin and linezolid, but susceptibilities of the various Nocardia spp. to beta-lactams, aminoglycosides, ciprofloxacin and clarithromycin varied markedly. Overall, there was a good correlation between the drug resistance patterns and the species identification established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
70
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 25 publications
15
70
2
5
Order By: Relevance
“…Usually nocardial therapy involves prolonged use of antimicrobials combined with surgical debridation/drainage, extirpation of foreign bodies and lavage of infected lesions using anti-septic solutions 2,10,19,25,26,30 . Long-term antimicrobial therapy is recommended due to intracellular localization of agent, development of pyogranulomatous inflammatory reaction and resistant pattern strains that lead to poor response to the conventional antimicrobial treatment 10,19,32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Usually nocardial therapy involves prolonged use of antimicrobials combined with surgical debridation/drainage, extirpation of foreign bodies and lavage of infected lesions using anti-septic solutions 2,10,19,25,26,30 . Long-term antimicrobial therapy is recommended due to intracellular localization of agent, development of pyogranulomatous inflammatory reaction and resistant pattern strains that lead to poor response to the conventional antimicrobial treatment 10,19,32 .…”
Section: Discussionmentioning
confidence: 99%
“…organisms show large variation in susceptibility in vitro to different antimicrobials. Sulfonamides-trimethoprim, amikacin and cephalosporins commonly show efficacy in human 3,25 and animal strains 26,45 . Antimicrobial susceptibility tested in 28 Nocardia strains in this trial showed that amikacin, ceftiophur, sulphamethoxazoletrimethoprim and gentamicin were the most-effective drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In current study, seven isolates identified as N. farcinica as first report of infections caused by this species from Iran. It has been reported to constitute 23.8%, 26.7%, 35.4% 44%, 60.3% and 33.3% and 21.6% of Nocardia isolates in France [14], Japan [28], Thailand [29], Belgium [30] [31], Germany [32] and Spain [16] respectively. Six of the clinical isolates were identified as N. wallacae as the first report of infections caused by the later species in Iran.…”
Section: Discussionmentioning
confidence: 99%